Clinical and functional characteristics of patients two years after being affected by the soybean asthma epidemic in Barcelona. Issue 9 (September 1994) - Sabrià, J; Antó, J M; Sunyer, J; Roca, J; Morell, F; Rodríguez-Roisín, R; Rodrigo, M J; Codina, R
Abstract : BACKGROUND–Patients affected during the asthma outbreaks caused by soybean dust inhalation in Barcelona presented with sudden onset of severe asthma followed by the rapid relief of symptoms after treatment. Two years after the epidemics ended, a case-control study was conducted in which the clinical, functional, and immunological characteristics of these asthma patients (a randomised sample of asthmatic patients admitted as emergency cases on epidemic days, n = 213) were compared with those of a control group (a random sample of asthmatic patients admitted as emergency cases for attacks of asthma on non-epidemic days, n = 170). METHODS–The study included the administration of the ATS-DLD78 standardised respiratory questionnaire, the measurement of atopy, and performance of spirometric tests and a methacholine inhalation test. RESULTS–Patients with epidemic asthma reported fewer symptoms of asthma, had attended emergency departments less frequently during the previous year for acute attacks of asthma, were taking fewer inhaled corticosteroids at the time of the study, and attended medical follow up less frequently than did the patients with non-epidemic asthma. However, the cases and controls showed no differences in ventilatory capacity or reactivity to the methacholine bronchoprovocation test. CONCLUSIONS–Two years after the end of the soybean epidemics, people affected by epidemic asthma had a favourable prognosis. This finding contrasts with a higher risk of life threatening asthma and death during the epidemics. This paradox could be the result of a complex interaction between host and conditions of exposure.